A test of Allen’s rule in ectotherms: the case of two south American melanopline grasshoppers (orthoptera: acrididae) with partially overlapping geographic ranges - Marti, Dardo Andrea (2008)
We studied the geographic variation of three morphometric characters in relation to body size in two South American grasshoppers (Acrididae), Dichroplus vittatus Bruner and D. pratensis Bruner to test Allen’s rule in these ectotherms. Since both species follow the converse to Bergmann’s rule owing to latitudinal and/or altitudinal variation in time available for growth and reproduction, geographic variation in body size proportions of protruding parts may obey to differential allometric growth in different geographic areas. Alternatively, it could refl ect true Allenian variation related to thermoregulation. Body proportions were studied by  correlation/regression analyses with geographic and climatic variables. In D. pratensis, body proportions increased with latitude and decreased with altitude. These results probably obey to the effects of water balance and seasonality on fi nal body size, and on the allometric growth of the three studied characters not being related to thermoregulation. In D. vittatus, a generally non-signifi cant trend towards the decrease of the mean proportions of all three characters with increasing latitude was observed. Nevertheless, also in this species, it is probable that the environmental gradient responds to seasonality factors (although not to water balance) that affect the length of growing season and, in consequence, body size and its allometric relationships. We conclude that the regularities in the geographic distribution of body proportions of D. pratensis and D. vittatus do not follow Allen’s rule in the sense of thermoregulation, and result from variables that determine growing season length and the allometric growth of different body parts. KEY WORDS: Allometry, body proportion, body size, Dichroplus, geographic variatio.